2022
DOI: 10.14245/ns.2142724.362
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Nerves Reconstruction After Surgical Resection of a Large Sacral Chordoma Restores the Urinary and Sexual Function and the Anal Continence

Abstract: Objective: Chordomas are slow-growing tumors, with a high tendency to local relapse. En bloc resection is related to the most favorable outcome in terms of survival but is frequently associated with permanent neurological deficits involving sphincters and sexual functions. In the present article, we describe an innovative technique of en bloc resection followed by reconstruction of the sacral nerves with nerve grafts. Methods:The chordoma was excised through a posterior approach after dividing the proximal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…14 The rectum is not involved anteriorly through the presacral fascia. 13,23 The most common presenting symptom is local pain 10 and tenderness resulting from periosteal stretching from cortical expansion, mass effect, and compression of neighboring structures. Increasing compression of nerve roots can impair reflex arcs and provokes multiradicular sensory deficits to the uni or bilateral buttocks, posterior thigh, leg, external genitalia, and perineum depending on the level of tumor extension.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The rectum is not involved anteriorly through the presacral fascia. 13,23 The most common presenting symptom is local pain 10 and tenderness resulting from periosteal stretching from cortical expansion, mass effect, and compression of neighboring structures. Increasing compression of nerve roots can impair reflex arcs and provokes multiradicular sensory deficits to the uni or bilateral buttocks, posterior thigh, leg, external genitalia, and perineum depending on the level of tumor extension.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Conventional chordoma, dedifferentiated chordoma and poorly differentiated chordoma. [3][4][5] Chordoma represents only 1-4% of all primary malignant bone neoplasms, [6][7][8][9][10][11] is the most common primary malignant tumor within the spine, 6 is the most common tumor of any type involving the sacrum, 6,[12][13][14][15] and approximately 50% of all chordomas are sacrococcygeal in origin. 6,13,16,17 Chordoma treatment is eminently surgical through wide or radical Cirugía de Columna | 2024; 2 (2): 104-111 resection (partial sacrectomy, total sacrectomy or extended sacrectomy), and is usually associated with important sequelae mainly related to sphincter control.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, We appreciate the interest in our article "Sacral nerves reconstruction after surgical resection of a large sacral chordoma restores the urinary and sexual function and the anal continence. " 1 The sacrifice of sacral nerves is often a necessary step if a benefit is to be given to the progression free survival rate, which results in a severe burden and deterioration of quality of life for patients with sacral chordoma.…”
mentioning
confidence: 99%
“…In the paper, the authors described a new technique, which is used for the first time in the field of sacral chordoma resection, that is, bulk resection of sacral chordoma, and then sacral nerve reconstruction with peripheral nerve transplantation. 4 The 54-year-old patient diagnosed with sacral chordoma, the authors marked the nerve roots in the proximal and distal part of the lesion with sutures, separated the proximal and distal sacral nerves, and resected the chordoma involving bilateral lower S1 sacral nerves (14 cm× 8 cm× 7 cm) through the posterior approach. After operation, the sural nerve of the bilateral leg was grafted, and the epineurial microsuture technique was used to connect the stump and the distal end of S2-S3-S4.…”
mentioning
confidence: 99%
“…Zheng et al [ 11 ] reported that 5 cases of sacral nerve root anastomosis were performed after block resection of sacral tumor, and only 2 cases showed improvement in limb, bladder and intestinal function. However, in the author’s article [ 4 ], only one case of functional improvement after nerve transplantation after tumor resection was described, which may be related to the surgeon’s experience, body healing ability etc. It does not have extensive maneuverability and outstanding representativeness.…”
mentioning
confidence: 99%